Understanding the effects of copolymerized cellulose nanofibers and diatomite nanocomposite on blend chitosan films. (1st November 2021) - Mujtaba, Muhammad; Fernández-Marín, Rut; Robles, Eduardo; Labidi, Jalel; Yilmaz, Bahar Akyuz; Nefzi, Houwaida
Abstract: Chitosan films lack various important physicochemical properties and need to be supplemented with reinforcing agents to bridge the gap. Herein, we have produced chitosan composite films supplemented with copolymerized (with polyacrylonitrile monomers) cellulose nanofibers and diatomite nanocomposite at different concentrations. The incorporation of CNFs and diatomite enhanced the physicochemical properties of the films. The mechanical characteristics and hydrophobicity of the films were observed to be improved after incorporating the copolymerized CNFs/diatomite composite at different concentrations (CNFs: 1%, 2% and 5%; diatomite: 10% and 30%). The antioxidant activity gradually increased with an increasing concentration (1–5% and 10–30%) of copolymerized CNFs/diatomite composite in the chitosan matrix. Moreover, the water solubility decreased from 30% for chitosan control film (CH-0) to 21.06% for films containing 30% diatomite and 5% CNFs (CNFs-D30-5). The scanning electron micrographs showed an overall uniform distribution of copolymerized CNFs/diatomite composite in the chitosan matrix with punctual agglomerations. Graphical abstract: Unlabelled Image Highlights: Chitosan films alone lack various important physicochemical properties. Films were produced with copolymerized CNFs and diatomite nanocomposite. CNFs and diatomite notably enhanced the physicochemical properties of the films. The films were visually transparent up to an acceptable level.